1999
DOI: 10.1017/s1461145799001509
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-dependent protein kinase in subtypes of major depression and normal volunteers

Abstract: We have shown a reduction in beta adrenoceptor-linked, cyclic AMP-dependent protein kinase [protein kinase A (PKA)] activity in fibroblasts of patients with major depression with melancholic features relative to normal volunteers. We evaluated a group of 35 patients with major depression subtyped by DSM-IV criteria as melancholic, atypical, and those not meeting either subtype designation ('non-subtyped') and 21 normal volunteers to ascertain whether or not the PKA activity abnormality was specific to melancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…The aim of the current study was to probe for differences in the 5-HT 2A receptormediated signal transduction pathway, using an ex vivo fibroblast cell culture model system. Previous studies in our laboratory have demonstrated significant differences in the adenylyl cyclase signaling pathway in melancholic subtype of depression vs controls and depressives with the atypical subtype (Shelton et al, 1996(Shelton et al, , 1999Manier et al, 2000). Since these results were found only in a subset of depressives, the differences could be masked in the total depressive patient population, underscoring the value of diagnostic subclassification.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The aim of the current study was to probe for differences in the 5-HT 2A receptormediated signal transduction pathway, using an ex vivo fibroblast cell culture model system. Previous studies in our laboratory have demonstrated significant differences in the adenylyl cyclase signaling pathway in melancholic subtype of depression vs controls and depressives with the atypical subtype (Shelton et al, 1996(Shelton et al, , 1999Manier et al, 2000). Since these results were found only in a subset of depressives, the differences could be masked in the total depressive patient population, underscoring the value of diagnostic subclassification.…”
Section: Introductionmentioning
confidence: 67%
“…Fibroblasts were cultured from skin biopsies, as described previously (Shelton et al, 1996(Shelton et al, , 1999. All samples have been subcultured for at least five passages in order to minimize any effect from exposure in vivo to factors such as hormones, transmitters, drugs, or other factors.…”
Section: Collecting and Culturing Of Human Fibroblastsmentioning
confidence: 99%
“…Thus, if GR signaling is impaired, CRH expression through P-CREB is enhanced and this effect is counteracted by venlafaxine (and perhaps also by other antidepressants) which reduces P-CREB (Rossby et al 1999). Still, other impairments in cAMP-PKA pathways may possibly exist in depression (Shelton et al 1999), including impaired CRE-regulated gene expression which can be restored by antidepressants. Since cross-talk between cAMP-PKA pathways and corticosteroid signaling is well documented, impaired corticosteroid receptor function could not only result from altered cAMP-PKA activity but may in turn account for disturbances in cAMP-PKA-elicited activation of CRE.…”
Section: Consequences For Future Drug Treatment Of Depression Currentmentioning
confidence: 99%
“…Accordingly, we have used differential display (Liang and Pardee, 1992) to contrast gene expression patterns in cultured fibroblasts from patients with major depression with melancholia vs normal volunteers and nonmelancholic depressives. The samples from patients with melancholia had previously been shown to have reduced PKA activity and CREB phosphorylation; the nonmelancholics and normal volunteers all had PKA-CREB-P within the normal range previously reported (Shelton et al, 1999;Manier et al, 2000). A strength of differential display is that it is capable of detecting both known and novel genes and does not require an a priori hypothesis.…”
Section: Introductionmentioning
confidence: 94%
“…Human fibroblasts as non-neuronal tissue express genes encoding proteins involved in monoaminergic-G-protein-coupled transduction cascades similar to the expression in neuronal tissue, for example, beta adrenoreceptors, 5HT 2A receptors, and G-proteins. Using human fibroblasts, our group has demonstrated abnormalities in the beta adrenoceptor-cyclic AMP-mediated activation of protein kinase A (PKA) and phosphorylation of the transcription factor cyclic AMP response element-binding protein (CREB) in patients with major depression, melancholic subtype, relative to normal volunteers and nonmelancholic depressives (Shelton et al, , 1999Manier et al, 1996Manier et al, , 2000. These findings are similar to the results from other investigators, including a decrease in the putative binding of cyclic AMP to PKA in post-mortem brains of patients with bipolar disorder (Rahman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%